Analysis of outcomes and renal recovery after adult living‐donor liver transplantation among recipients with hepatorenal syndrome. Issue 10 (8th June 2022) - Park, Cheon‐Soo; Yoon, Young‐In; Kim, Nayoung; Hwang, Shin; Ha, Tae‐Yong; Jung, Dong‐Hwan; Song, Gi‐Won; Moon, Deok‐Bog; Ahn, Chul‐Soo; Park, Gil‐Chun; Kim, Ki‐Hun; Cho, Yong‐Pil; et al.
Abstract: When timely access to deceased‐donor livers is not feasible, living‐donor liver transplantation (LDLT) is an attractive option for patients with hepatorenal syndrome (HRS). This study's primary objective was to describe outcomes after LDLT among HRS recipients, and the secondary objective was to determine predictors of poor renal recovery after LDLT. This single‐center, retrospective study included 2185 LDLT recipients divided into HRS ( n = 126, 5.8%) and non‐HRS ( n = 2059, 94.2%) groups. The study outcomes were survival and post‐LT renal recovery. The HRS group had a higher death rate than the non‐HRS group (17.5% vs. 8.6%, p < 0.001). In the HRS group, post‐LT renal recovery occurred in 69.0%, and the death rate was significantly lower in association with HRS recovery compared with non‐recovery (5.7% vs. 43.6%, p < 0.001). Multivariable analysis indicated that post‐LT sepsis ( p < 0.001) and non‐recovery of HRS ( p < 0.001) were independent negative prognostic factors for survival. Diabetes mellitus ( p = 0.01), pre‐LT peak serum creatinine ≥3.2 mg/dl ( p = 0.002), time interval from HRS diagnosis to LDLT ≥38 days ( p = 0.01), and post‐LT sepsis ( p = 0.03) were important negative prognostic factors for renal recovery after LDLT. In conclusion, post‐LT renal recovery was important for survival, and the interval from HRS to LDLT was significantly associated with post‐LT renal recovery. Abstract : When timely access to deceased‐donor livers is not available for candidates with hepatorenal syndrome, expeditious living‐donor liver transplantation can reduce the risk of death or permanent renal failure. Selzner and Wong comment on page 2291